Performance Evaluation of a Novel Ultrafast Molecular Diagnostic Device Integrated With Microfluidic Chips and Dual Temperature Modules - Lin, Shan; Song, Xiaojun; Zhu, Kun; Shao, Quanyu; Chen, Yinhang; Cheng, Wei; Lei, Zhijing; Chen, Yu; Luo, Yun; Jin, Dazhi (Frontiers in Bioengineering and Biotechnology, 2022)
Ultrafast, portable, and inexpensive molecular diagnostic platforms are critical for clinical diagnosis and on-site detection. There are currently no available real-time polymerase chain reaction (PCR) devices able to meet the demands of point-of-care testing, as the heating and cooling processes cannot be avoided. In this study, the dual temperature modules were first designed to process microfluidic chips automatically circulating between them. Thus, a novel ultrafast molecular diagnostic real-time PCR device (approximately 17 min and 22 min for DNA and RNA detection, respectively) with two channels (FAM and Cy5) for detection of 12 targets was developed. The device contained three core functional components, including temperature control, optics, and motion, which were integrated into a portable compact box. The temperature modules accurately control temperature in rapid thermal cycles with less than ±0.1℃, ±1℃ and ±0.5℃ for the temperature fluctuation, uniformity, and error of indication, respectively. The average coefficient of variation(CV) of the fluorescence intensity (FI) for all 12 wells was 2.3% for FAM and 2.7% for Cy5. There was a good linear relationship between concentrations of fluorescent dye and the FIs of FAM and Cy5(R2 = 0.9990 and 0.9937), and the average CVs of Ct values calculated by the embedded software were 1.4% for FAM and Cy5, respectively. The 100 double-blind mocked sputum and 249 clinical stool samples were analyzed by the ultrafast real-time PCR device in comparison with the DAAN Gene SARS-CoV-2 kit run on the ABI 7500 instrument and Xpert C. difficile/Epi, respectively. Among the 249 stool samples, the ultrafast real-time PCR device detected toxigenic C. difficile in 54 samples (54/249, 21.7%) with a specificity and positive predictive values of 99.0% and 96.3%, which were higher than the Xpert C. difficile/Epi values of 94.4% and 88.1% (P > 0.05). The ultrafast real-time PCR device detected 15 SARS-CoV-2 positive samples, which has a 100% concordance with that obtained by the DAAN Gene SARS-CoV-2 kit. This study demonstrated that the ultrafast real-time PCR device integrated with microfluidic chips and dual temperature modules is an ultrafast, reliable, easy-to-use, and cost-effective molecular diagnostic platform for clinical diagnosis and on-site testing, especially in resource-limited settings.